‘Do Good, Expect the Worst’: The Indirect Effect of Social Cynicism on Prosocial Behavior via Empathy and Trust - Denis Coca; Alin Gavreliuc (International Review of Social Psychology, 2025)
Do cynical individuals still engage in prosocial behaviors when they expect the worst from others? While prior research suggests cynical beliefs reduce empathy and trust—key drivers of prosociality—this pathway remains underexplored. We tested four structural equation models (manifest and latent) using data from 239 Romanian adults. Only the manifest model supported an indirect effect via empathic concern; latent models accounting for measurement error did not. This discrepancy highlights how item-level variance may inflate observed relationships. Theoretical and methodological implications are discussed considering the social axioms model and empathy-trust mechanisms in prosocial behavior.